Simulation of Three Points Bending SS316 to Know Mechanical Stress with ABAQUS - Janah, Yulia Miftah Hul; Mustari, Asril Pramutadi Andi (Indonesian Journal of Physics, 2024)
The operating life of the Gen IV nuclear reactor, which is 60 years, will require material upgrades over a very long period of time. Stability, high reliability, adequate resources, and easy fabrication, as well as weldability, environmental impact, and aging, are other important aspects to consider during the material selection process. SS316 is currently in demand as a structural material for future Gen IV nuclear power plants operating at high temperatures. Although grade SS316 has been studied for current nuclear service conditions and other conventional applications, better data and models for long-term high-temperature properties are needed, especially with regard to primary to tertiary creep strain and creep-fatigue response. The three-point bending test on SS316 material can be modeled with ABAQUS simulation. The purpose of this study is to compare the distribution of the voltage profile for parameters at room temperature (25°C) and high temperature (650°C). In addition, simulations were conducted to compare the effects of load displacement (U2) variations, namely 25, 20 and 15 for each temperature. ABAQUS is an engineering simulation program based on finite element methods that can solve simple linear analysis problems to complex nonlinear simulations. ABAQUS comes with a comprehensive database of elements that can model almost any geometry. This simulation can describe the voltage profile that is spread over the geometry after the required parameters are entered. From the results obtained, the greater the displacement of U2, the smaller the maximum stress that can be resisted by the material. It also shows that at higher temperatures (650°C), materials tend to experience a decrease in strength or maximum stress compared to lower temperatures (25°C). So the material under test experiences a decrease in maximum strength or stress as the temperature increases and the U2 displacement.